(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In recent years, educators have increasingly explored innovative and technology-enhanced teaching strategies to improve student engagement, particularly in subjects that are often perceived as challenging or less engaging, such as Social Studies. One of the most prominent approaches is Game-Based Learning (GBL), which integrates game design elements and principles into instructional activities to create more interactive, meaningful, and student-centered learning experiences. Grounded in motivational and constructivist learning theories, Game-Based Learning emphasizes active participation, experiential learning, and intrinsic motivation. From a theoretical perspective, GBL aligns with constructivist ideas that learners build knowledge through active engagement and interaction with content, as well as self-determination theory, which highlights the importance of autonomy, competence, and relatedness in sustaining student motivation and engagement. These frameworks help explain why game-based approaches may positively influence students’ behavioral, emotional, and cognitive engagement in learning environments.